Sleep characteristics of elite youth athletes: a clustering approach to optimize sleep support strategies - Suppiah, H. T.; Swinbourne, R.; Wee, J.; Tay, V.; Gastin, P. (International Journal of Sports Physiology and Performance, 2021)
Purpose: Elite athletes experience chronic sleep insufficiency due to training and competition schedules. However, there is little research on sleep and caffeine use of elite youth athletes and a need for a more nuanced understanding of their sleep difficulties. This study aimed to (1) examine the differences in sleep characteristics of elite youth athletes by individual and team sports, (2) study the associations between behavioral risk factors associated with obstructive sleep apnea and caffeine use with sleep quality, and (3) characterize the latent sleep profiles of elite youth athletes to optimize the sleep support strategy.